Microbial shifts in dental plaque of children with severe early childhood caries following comprehensive dental treatment under general anesthesia - Wang, Xinyue; Huang, Hui; Ma, Qizhao; Zou, Jing (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveTo elucidate the microbial diversities and compositions of dental plaque in children with severe early childhood caries (S-ECC) before and after comprehensive dental treatment under general anesthesia, contributing evidence for the reestablishment of oral microecological balance.DesignTwenty children aged 2.2-5.5 years diagnosed with S-ECC without systemic diseases were enrolled in this study. Dental plaque samples were collected before and after treatment, analyzed using high-throughput sequencing on the Illumina Miseq platform. Bioinformatics methods were employed to compare the dental plaque microbial diversity and compositions differences before and after comprehensive dental treatment under general anesthesia.ResultsSignificant enhancements in dental plaque microbial diversity were observed post-comprehensive treatment (P < 0.05). At the phylum level, the relative abundance of Actinobacteria significantly decreased after treatment (P < 0.05). At the genus level, the relative abundance of Streptococcus, Neisseria, and Rothia significantly declined (P < 0.05), while Prevotella showed a significant increase after treatment (P < 0.05).ConclusionsFollowing comprehensive dental treatment under general anesthesia, children with S-ECC exhibit significant changes in the microbial diversity and composition of dental plaque, indicating a shift towards a more balanced oral microecological state. This study highlights the importance of dental intervention in positively altering oral microbiota.